2013
DOI: 10.3109/07357907.2012.762779
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Aberrancies and Hepatocellular Carcinoma: Studies in the MDR2 Gene Knockout Mouse

Abstract: Studies show that lysophosphatidic acid (LPA) reprogramming is associated with the development of hepatocellular carcinoma (HCC). This manuscript evaluates the MDR2(-/-) model of HCC as a tool to examine the role of LPA reprogramming in the initiation/progression of HCC and identify novel treatment targets. Hepatic tumors developed in MDR2(-/-) mice between 9-12 m and serum LPA levels were greater in MDR2(-/-) when compared to controls. Blocking LPA biosynthesis/signaling significantly reduced tumor burden. LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Moreover, we have previously shown that LPA variants were able to differentiate between liver disease and patients with HCC [ 59 ]. Interestingly, these data are consistent with our current, and previous [ 6 ], studies in MDR2 −/− mice where LPA is not only elevated contemporaneous with HCC, but the LPA 20:4 and 18:2 variants are highly consistent with data from the clinical populations with HCC. Currently the precise role and mechanism connecting LPA to HCC is not fully understood.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, we have previously shown that LPA variants were able to differentiate between liver disease and patients with HCC [ 59 ]. Interestingly, these data are consistent with our current, and previous [ 6 ], studies in MDR2 −/− mice where LPA is not only elevated contemporaneous with HCC, but the LPA 20:4 and 18:2 variants are highly consistent with data from the clinical populations with HCC. Currently the precise role and mechanism connecting LPA to HCC is not fully understood.…”
Section: Discussionsupporting
confidence: 93%
“…In patients transplanted with cancer in whom the explant shows a greater disease burden than that noted on pre-transplant imaging putting them at a higher risk for cancer recurrence 11 C-acetate imaging may provide some advantage over CT or MRI when used for surveillance in post-transplant patients considered at higher risk for recurrence and in whom clinical trials of novel immunosuppressant protocols post-transplant would become relevant. The MDR2 -/- mouse model of HCC provides a murine model whereby new paradigms of HCC diagnosis and targeted therapy can be evaluated [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations